An Uncommon Textbook: Review of Common Sense Mathematics by Ethan Bolker and Maura Mast - Bernard L. Madison (Numeracy, 2019)
Ethan D. Bolker and Maura B. Mast. 2016. Common Sense Mathematics.(Washington DC.: Mathematics Association of America) ISBN-13: 978-1-93951-210-9.